2022
DOI: 10.3389/fmicb.2022.953424
|View full text |Cite
|
Sign up to set email alerts
|

Autotoxin affects the rhizosphere microbial community structure by influencing the secretory characteristics of grapevine roots

Abstract: Autotoxins secreted by roots into the soil can trigger rhizosphere microecological imbalances and affect root secretory properties resulting in conditions such as replanting disease. However, information on the effect of autotoxins on root secretion characteristics and regulation of the composition of rhizosphere microorganisms by altered root exudates is limited. In this study, autotoxin ρ-hydroxybenzoic acid (4-HBA) was added to the soil of potted grapevine seedlings, CO2 pulse-labeling, and DNA stable isoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 89 publications
2
7
0
1
Order By: Relevance
“…Still, it increased the presence and abundance of bene cial belowground fungal such as Mortieralla, Exophiala, Paraboeremia, Bionectria, Clitopilus, Marasmius, Pyrenochaetopsis and Trichoderma compared to the Mono cropping system. The ndings of these studies are in line with previous studies, which indicated that bene cial fungi have a positive impact on agroecosystem [31], [107]- [109]. For example, Mortierella spp.…”
Section: Effect and Role Of Push-pull Cropping System On Soil And Mai...supporting
confidence: 90%
See 2 more Smart Citations
“…Still, it increased the presence and abundance of bene cial belowground fungal such as Mortieralla, Exophiala, Paraboeremia, Bionectria, Clitopilus, Marasmius, Pyrenochaetopsis and Trichoderma compared to the Mono cropping system. The ndings of these studies are in line with previous studies, which indicated that bene cial fungi have a positive impact on agroecosystem [31], [107]- [109]. For example, Mortierella spp.…”
Section: Effect and Role Of Push-pull Cropping System On Soil And Mai...supporting
confidence: 90%
“…The presence of these bacteria genera in PPT soils and maize-roots implies that PPT positively in uences below-ground microbial populations compared to Mono. Similar ndings have been observed in various other cropping systems, including long-term intercropping systems, push-pull experimental plots, multiple cropping systems, crop rotation, and cover cropping [7], [8], [31], [79]. Nitrospira were found more in PPT, and these types of bacteria are capable of carrying out nitri cation, which involves the oxidation of ammonia in a single organism [3], [22], [25], [85].…”
Section: Effect and Role Of Push-pull Cropping System On Soil And Mai...supporting
confidence: 73%
See 1 more Smart Citation
“…Gibberella and Trichocladium were more abundant in samples obtained after continuous cropping for years than in those obtained after 1 year [50]. Previous results showed that Fusarium and Gibberella act as plant pathogens [51,52].…”
Section: Discussionmentioning
confidence: 80%
“… Wang et al (2023) also found differences in community composition and multifunctionality between healthy and Alternaria solani -infected potato rhizosphere soils. The rootstock diseases of tobacco are mostly caused by fungi ( Modjo and Hendrix, 1986 ; Gonzalez et al, 2011 ; Yang et al, 2020 ), and the pathogens may affect the soil microbial community by changing the rhizosphere secretions of crops in addition to directly attaching to the root surface and contacting the soil ( Liu et al, 2022 ). Of course, such findings do not negate the conclusion that regional differences have a significantly greater impact than rootstock diseases in the analysis of microbial diversity, core taxa, and co-occurrence networks.…”
Section: Discussionmentioning
confidence: 99%